2010
DOI: 10.3390/medicina46090091
|View full text |Cite
|
Sign up to set email alerts
|

The coagulation system changes in patients with chronic heart failure

Abstract: Though heart failure can mainly be caused by systolic or diastolic dysfunction, the impairments of the neurohormonal, immune, and hemostatic systems are observed too. Therefore, it is not easy to determine etiology of the syndrome. Parameters that can be helpful to predict chronic heart failure, to evaluate its course and the risk of complications are still being searched. The aim of this article is to review the recent studies in order to find the links between the coagulation system and the development of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 26 publications
(33 reference statements)
0
33
0
2
Order By: Relevance
“… 4 - 6 Other studies have also observed increased coagulation factors, fibrinolysis, and platelet activation. 7 The ultimate underlying mechanism may be due to tissue ischemia, stagnant blood flow, and increased α-adrenergic activity in CHF leading to DIC. Ventricular thrombi can be a consequence of activated coagulation pathway but may also “consume” coagulation factors locally leading to severe DIC.…”
Section: Discussionmentioning
confidence: 99%
“… 4 - 6 Other studies have also observed increased coagulation factors, fibrinolysis, and platelet activation. 7 The ultimate underlying mechanism may be due to tissue ischemia, stagnant blood flow, and increased α-adrenergic activity in CHF leading to DIC. Ventricular thrombi can be a consequence of activated coagulation pathway but may also “consume” coagulation factors locally leading to severe DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation abnormalities have been reported in patients that show different severities of heart diseases in human (7,19) and veterinary medicine (8,10,20), and thus therapeutic approaches have been suggested to protect patients from these problems (17). Coagulation activation and related complications such as thromboembolism were reported, especially in cats with hypertrophic cardiomyopathy (17,21).…”
Section: Discussionmentioning
confidence: 99%
“…The top GeneGo process network was ‘Blood coagulation’ ( Figure C ), as many of the identified biomarkers are known to be involved in this process: coagulation factor IX, coagulation factor X, prothrombin, antithrombin‐III, vitamin K‐dependent protein C, vitamin K‐dependent protein S, and alpha‐2‐antiplasmin. A link between the development of chronic HF and abnormalities in blood coagulation has been shown previously . Higuchi et al found that protein S was up‐regulated in mouse myocardium in different aetiological models of HF, and hypothesized that this up‐regulation may have a protective role in the failing heart .…”
Section: Discussionmentioning
confidence: 71%